Предмет: Алгебра,
автор: mycuufuc
УПРОСТИТЕ ВЫРАЖЕНИЕ
Номер 1
Даю 24 балла
Приложения:
Ответы
Автор ответа:
0
Ответ:
+ 1
Объяснение:
(((x^1.5 - 1) / (x^0.5 - 1)) + x^0.5) / ((x-1) / (x^0.5 - 1)) = (x sqrt (x) - 1 + x - sqrt (x)) * 1 / (sqrt (x) -1)(sqrt (x) + 1) = (x + 2 sqrt (x) + 1) / (sqrt (x) + 1) = (sqrt (x) + 1)^2 / (sqrt (x) + 1) = + 1
Похожие вопросы
Предмет: Английский язык,
автор: alenkaqw
Предмет: Русский язык,
автор: Nikuliihka
Предмет: Русский язык,
автор: lenok20032804
Предмет: Математика,
автор: pusya225561
Предмет: Литература,
автор: kucolca